Effects of Pioglitazone versus Simvastatin on Biomarkers of Inflammation in Patients on High Cardiovascular Risk - Hanefeld, M.; Schaper, F.; Appelt, D.; Fuchs, W. (Hormone and Metabolic Research, 2011)
High levels of fetuin-A has been linked to cardiovascular disease, possibly via modulating low-grade systemic inflammation. We performed a subanalysis from the PIOSTAT study to investigate a possible link between fetuin-A and the inflammatory biomarker hs-CRP. 66 nondiabetic individuals at cardiovascular risk were randomized to either pioglitazone, simvastatin, or the combination of both, and followed for 12 weeks. At study endpoint, correlations between serum fetuin-A, hs-CRP, blood lipids, PAI-1, MMP-9, HOMA-IR, and liver transaminases were investigated by Spearman rank correlation. Changes in fetuin-A concentration did not correlate to changes in hs-CRP (r=0.19, p=0.16). A positive correlation was found for change of HOMA-IR value (r=0.33, p=0.01) and for the AST/ALT ratio (p<0.05). Our data suggest that the previously observed correlation between elevated circulating fetuin-A and hs-CRP in epidemiological studies may not reflect a causal relationship in nondiabetic patients on high cardiovascular risk.